2018
DOI: 10.1200/jco.2017.75.9134
|View full text |Cite
|
Sign up to set email alerts
|

Brachytherapy-Based Radiotherapy and Radical Prostatectomy Are Associated With Similar Survival in High-Risk Localized Prostate Cancer

Abstract: Purpose There are no randomized trials to guide treatment decisions between radiotherapeutic and surgical options for patients with high-risk localized prostate cancer. Comparative studies have been limited by their ability to match patients on the basis of pretreatment prognostic variables and to adjust for the cancer-related, medical, and socioeconomic differences between patients who choose radiotherapeutic or surgical approaches. Methods We analyzed the outcome of all patients in the National Cancer Databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 22 publications
4
61
0
Order By: Relevance
“…This was for 11 catheters (median value, range 7-20) the case, when compared to final plans generated using the default initialization of HIPO. On the other hand, the HIPO CVT_adaptive plans differed in ten catheter positions (median value, range [6][7][8][9][10][11][12][13][14][15][16][17][18], when compared to corresponding final HIPO default_adaptive plans.…”
Section: D1 Hipo Execution In Adaptive Modementioning
confidence: 99%
See 1 more Smart Citation
“…This was for 11 catheters (median value, range 7-20) the case, when compared to final plans generated using the default initialization of HIPO. On the other hand, the HIPO CVT_adaptive plans differed in ten catheter positions (median value, range [6][7][8][9][10][11][12][13][14][15][16][17][18], when compared to corresponding final HIPO default_adaptive plans.…”
Section: D1 Hipo Execution In Adaptive Modementioning
confidence: 99%
“…Prostate HDR brachytherapy (HDRBT) has been established as a significant treatment method for the radiotherapy of prostate cancer (PCA) in a variety of protocols. [1][2][3][4] HDRBT is often used either as a local dose escalation technique in a boost set-up in combination with external beam radiotherapy (EBRT) for intermediate-and high-risk-PCA [5][6][7][8] or as monotherapy for localized prostate cancer (low-intermediate risk and selective high-risk PCA cases). [9][10][11][12][13][14][15] During the last two decades, significant innovations such as improved ultrasound (U/S) image quality, high resolution three-dimensional (3D) U/S volume acquisition, and catheter reconstruction on live U/S-imaging have been achieved in the field of 3D intraoperative ultrasound HDR-BT for PCA.…”
Section: Introductionmentioning
confidence: 99%
“…However, only one-fifth of CaPSURE patients had clinically significant cancer. Although the most recent study showed a significant benefit of radical prostatectomy over radiotherapy among young (age ≤65) men [7], several other studies found that radiation therapy was as effective as radical prostatectomy for high-risk cancer treatment [8,9]. Despite the debate over the benefit of these definitive treatments, whether there is a treatment preference among older men is not well documented.…”
Section: Introductionmentioning
confidence: 99%
“…In a population‐based retrospective study involving 42 576 men in the National Cancer Database, Ennis et al. reported that there were no differences in overall survival between men with high‐risk PCa treated with RP and those treated with EBRT + BT plus ADT, but men treated with EBRT plus ADT had significantly lower overall survival. In a separate retrospective study pooling 1 809 men with Gleason 9–10 PCa across 12 tertiary institutions in the USA and Norway, Kishan et al.…”
mentioning
confidence: 99%
“…Among the men who opt for RT, not all are suitable for BT boost because of pre‐existing urethral strictures, significant BOO, previous TURP, or large prostate volume; these men will be more appropriately treated with EBRT alone. However, with an increasing body of evidence supporting improved oncological outcomes with EBRT + BT over EBRT alone , the addition of BT boost, in the form of HDR or LDR therapy, to EBRT should be considered in all men with high‐risk PCa who opt for RT. In fact, it may be considered suboptimal care to not refer these patients for discussion and evaluation for BT boost, particularly the younger cohort.…”
mentioning
confidence: 99%